Ten tips to reduce fracture risk by non-pharmacologic interventions in CKD-associated osteoporosis - Ditte Hansen; Hanne Skou-Jørgensen; Mehmet Kanbay; Maria Fusaro; Louise Salomo; Susanne Fleig; Stig Molsted; Jesper Ryg; Mathias Haarhaus; Pieter Evenepoel (Clinical Kidney Journal, 2026)
Abstract Chronic kidney disease (CKD)-associated osteoporosis is present in approximately 25% of all patients with CKD. The occurrence increases as kidney function declines, with prevalences up to 75% in elderly dialysis patients. It is often undiagnosed due to the perception that limited treatment options are available for this condition. This inappropriate assumption leads to diagnostic and therapeutic nihilism. The effect size of pharmacological interventions on bone mineral density in patients with CKD is comparable or higher than in other forms of osteoporosis. Non-pharmacological interventions can improve bone strength and fracture risk in addition to pharmacological interventions. Importantly, they are often applicable to patients with CKD without restrictions, with some specific considerations in end-stage kidney disease. Due to the increased prevalence of modifiable risk factors for fragility fractures in CKD, non-pharmacological interventions should be provided to all patients with CKD-associated osteoporosis. We review current literature and describe ten tips of non-pharmacological interventions with the potential to modify fracture risk in CKD patients: Appropriate intake of calcium and vitamin D, adequate nutrition and protein intake, avoidance of smoking and alcohol, medication review, reinforcement of exercise, reducing risk of home hazards, prevention of orthostatic hypotension, take care of neuropathy, and determine fall risk as well as implementing fracture liaison services are all actions of relevance to the patient with CKD-associated osteoporosis. Like in the general population, non-pharmacological interventions should be the first option to consider when osteoporosis is diagnosed. With this paper, we suggest how this should be tailored to the patient with CKD.